Synthesis of Tetracyclic Flavonoids via Palladium-Catalyzed Intramolecular Oxidative Cyclization - Ayyagari, Narasimham; Belani, Jitendra D. (Synlett, 2014)
Palladium-catalyzed oxidative cyclization of terminal-olefin-tethered phenols was achieved in good yields (61–90% yields). The reaction was optimized and White catalyst {[1,2-bis-(phenylsulfinyl)ethane]palladium(II)acetate} provided the best yield in the presence of benzoquinone as an oxidant. The reaction tolerated both electron-donating and electron-withdrawing substituents on the substrates, and the structure of the tetracyclic flavonoids was confirmed using single-crystal X-ray analysis. The study represents the first example of successful allylic C–H activation/ C–O bond formation using terminal-olefin-tethered phenols.
Keywords: allylic C–H activation; palladium; phenol; flavonoids; C–O bond formation